Remaja di era modern: perspektif dan strategi pastoral - Sugianto, Paulus; David, Bryan; Susana, Mulyani; Stepanus, Stepanus (Sekola Tinggi Teologi Sangkakala Jakarta, 2024)
ABSTRACTAdolescence is a turbulent transition period, where individuals experience significant changes in mental, emotional, social, and physical aspects. During this period, adolescents often face various problems, both caused by their own actions and by external conditions such as parental divorce. In Indonesia, common moral crises include honesty, responsibility, and discipline. Education from parents, schools, and churches plays a crucial role in accompanying adolescents. This study uses a descriptive qualitative approach with data collection through interviews with adolescent mentors and literature reviews. This method aims to provide an in-depth and holistic picture of the phenomenon being studied, with researchers as the main instrument in obtaining the necessary data. The church has a responsibility to disciple each of its members, including the younger generation and adolescents. The church must be more proactive in implementing a discipleship-based curriculum and understanding the developmental needs of adolescents. Keywords: Adolescents, Modern era, Perspective, Strategy, Pastoral. ABSTRAKMasa remaja merupakan periode transisi yang penuh gejolak, di mana individu mengalami perubahan signifikan dalam aspek mental, emosional, sosial, dan fisik. Selama masa ini, remaja sering menghadapi berbagai permasalahan, baik yang disebabkan oleh tindakan mereka sendiri maupun oleh kondisi eksternal seperti perceraian orang tua. Di Indonesia, krisis moral yang umum meliputi kejujuran, tanggung jawab, dan disiplin. Pendidikan dari orang tua, sekolah, dan gereja memainkan peran krusial dalam mendampingi remaja. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui wawancara dengan pembina remaja dan kajian literatur. Metode ini bertujuan untuk memberikan gambaran mendalam dan holistik tentang fenomena yang diteliti, dengan peneliti sebagai instrumen utama dalam memperoleh data yang diperlukan. Gereja memiliki tanggung jawab untuk memuridkan setiap anggotanya, termasuk generasi muda dan remaja. Gereja harus lebih proaktif dalam menerapkan kurikulum berbasis pemuridan dan memahami kebutuhan perkembangan remaja. Kata Kunci: Remaja, Era modern, Perspektif, Strategi, Pastoral.